2015
DOI: 10.1016/j.vaccine.2014.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the immunogenicity and safety of polysaccharide and protein-conjugated pneumococcal vaccines among the elderly aged 80 years or older in Japan: An open-labeled randomized study

Abstract: An open-labeled randomized study was conducted to compare the immunogenicity and safety of polysaccharide (PPV23) or protein-conjugated pneumococcal vaccine (PCV7) among the elderly aged 80 years or older. A total of 105 nursing home residents were enrolled in this study. We analyzed the geometric mean concentration (GMC) of serotype-specific immunoglobulin G (IgG) and the geometric mean titer (GMT) of the opsonization index (OI) for serotypes 4, 6B, 9V, 14, 18C, 19F, and 23F. The GMCs of serotype-specific IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The reason for the discrepant results of these two studies remains unclear. A randomized study of nursing home residents Ն80 years old found that both PPV23 and PCV7 were immunogenic in this population, with the conjugate vaccine resulting in higher IgG levels and opsonic activity for some serotypes and both vaccines equally immunogenic for others (80). The effects of single-dose versus boosted vaccination, in various combinations, have been assessed in a number of studies but with conflicting results (reviewed in reference 81).…”
Section: Pneumococcal Vaccines Are Immunogenic In Older Peoplementioning
confidence: 99%
“…The reason for the discrepant results of these two studies remains unclear. A randomized study of nursing home residents Ն80 years old found that both PPV23 and PCV7 were immunogenic in this population, with the conjugate vaccine resulting in higher IgG levels and opsonic activity for some serotypes and both vaccines equally immunogenic for others (80). The effects of single-dose versus boosted vaccination, in various combinations, have been assessed in a number of studies but with conflicting results (reviewed in reference 81).…”
Section: Pneumococcal Vaccines Are Immunogenic In Older Peoplementioning
confidence: 99%
“…Finally, a study in subjects 80 years of age in Japan showed that PCV7 serotypes 4, 6B, 9V, 14, 18C, 19F, and 23F elicited higher functional antibody responses in PCV7 compared with PPSV23 recipients; these differences were significantly higher for serotypes 4, 9V, 18C, and 23F. 43 It is particularly reassuring that elderly Japanese subjects 80 years of age are able to mount higher functional antibody responses after PCV7 compared with PPSV23, despite reports of immunosenescence in the elderly. 44 As in other studies with PCV13, 12,19,45 in the current study, PCV13 was shown to have an acceptable safety and reactogenicity profile.…”
Section: Discussionmentioning
confidence: 95%
“…In our evaluation of serotype-specific IgG antibodies and serotype-specific OIs between PPV23 and PCV7 for pneumococcus vaccine-naïve elderly people (≥80 years of age), 90 both PPV23 and PCV7 elicited increases in IgG and OI. Meanwhile, PCV7 was more potent than PPV23 in terms of its immunogenicity against 4 serotypes out of the 7 included in PCV7 (serotypes 4, 9V, 18C, and 23F).…”
Section: Serotype Of Streptococcus Pneumoniaementioning
confidence: 93%